2015
DOI: 10.1002/pits.21877
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Competencies Among School Psychology Trainers and Practitioners: What Matters?

Abstract: Increasingly, professional training programs are dealing with the need for competency‐based assessments of student learning outcomes. This is particularly challenging in fields such as school psychology, with competencies identified by multiple accrediting bodies and state requirements. The primary goal of this study was to examine the degree to which competencies espoused by differing accrediting bodies are perceived as important among school psychologists. One hundred nineteen participants responded to quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The evaluation of specific competencies in the area of Health Service Psychology (HSP) has received increased attention over the past several years (e.g., Belar, 2009; Daly et al, 2011; Fenning et al, 2015; Fouad et al, 2009). For instance, in their assessment of the beliefs of school psychology faculty and practitioners regarding competencies and skills required by accrediting agencies (e.g., APA and NASP), Fenning et al (2015) found that assessment was rated “Very Important” or “Extremely Important” by a majority of participants. This level of competency importance is reflected in the actual practice of school psychology.…”
Section: Assessment Practices Of School Psychologymentioning
confidence: 99%
“…The evaluation of specific competencies in the area of Health Service Psychology (HSP) has received increased attention over the past several years (e.g., Belar, 2009; Daly et al, 2011; Fenning et al, 2015; Fouad et al, 2009). For instance, in their assessment of the beliefs of school psychology faculty and practitioners regarding competencies and skills required by accrediting agencies (e.g., APA and NASP), Fenning et al (2015) found that assessment was rated “Very Important” or “Extremely Important” by a majority of participants. This level of competency importance is reflected in the actual practice of school psychology.…”
Section: Assessment Practices Of School Psychologymentioning
confidence: 99%
“…Perhaps part of the reason for the lack of widespread integration of advocacy education within graduate programs may be linked to the importance that faculty members place on preparing their students to be advocates. In a recent survey of school psychologists about their perceptions of the most important competencies for practice, Fenning et al (2015) found that the largely faculty- and school-based practitioner sample (making up 79% and 11% of participants, respectively) considered advocacy, although still important, among the least highly rated activities. Their sample considered the activities associated with traditional school psychology practice (e.g., assessment, intervention) relatively more important than advocacy.…”
mentioning
confidence: 99%